2018
DOI: 10.3389/fmicb.2018.02897
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Microbiome Signatures and Short-Chain Fatty Acids in Mouse, Rat, Non-human Primate, and Human Feces

Abstract: Gut microbiome plays a fundamental role in several aspects of host health and diseases. There has been an exponential surge in the use of animal models that can mimic different phenotypes of the human intestinal ecosystem. However, data on host species-specific signatures of gut microbiome and its metabolites like short-chain fatty acids (SCFAs; i.e., acetate, propionate, and butyrate) and lactate in these models and their similarities/differences from humans remain limited, due to high variability in protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 54 publications
11
174
0
3
Order By: Relevance
“…OTU 784, Akkermansia, was not present when only assessing the microbiome of cat and dog owners, though this genera has previously been identified in rodents (Nagpal et al, 2018) and reptiles (Campos et al, 2018). Akkermansia was the only differentially abundant OTU we were able to tentatively to the species level.…”
Section: Discussionmentioning
confidence: 64%
“…OTU 784, Akkermansia, was not present when only assessing the microbiome of cat and dog owners, though this genera has previously been identified in rodents (Nagpal et al, 2018) and reptiles (Campos et al, 2018). Akkermansia was the only differentially abundant OTU we were able to tentatively to the species level.…”
Section: Discussionmentioning
confidence: 64%
“…However, for our findings to be clinically relevant, it needs to be first established that the mouse gut microbiome is, to a sufficient degree, reflective of the human gut microbiome. Previous studies have reported predominantly high relative abundances of the Bacteroidetes phylum in both mouse and human gut microbiomes [43][44][45][46]. Furthermore, there is evidence that B. vulgatus isolates from human and other animal hosts are indistinguishable based on their 16S rRNA gene sequences [47], suggesting phylogenetic proximity between mouse-and human-gut resident B. vulgatus strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, how such findings resonate with the results observed in our rat model of AKI remains unknown, as the species of Prevotella copri and Faecalibacterium prausnitzii were observed to be quantitatively reduced. Although the human gut microbiome might differ significantly from that in rat, due to differences in the relative abundance of many bacterial clades, a considerable fraction (not limited to major phyla) and many common genera are, however, extensively shared [58]. Consequently, this allows us a greater scope to extrapolate the findings from our working rat model towards a human context, with a view to dissect the potential relationship between the human microbiome and AKI/CKD progression, with proper accuracy and effect.…”
Section: Discussionmentioning
confidence: 99%